Implementing an Evidence-Based Practice Project in the Prevention of Peripheral Intravenous Site Infiltrations in Children. Issue 6 (November 2015) - Taylor, John T.
Abstract : More than 90% of hospitalized patients require peripheral intravenous (IV) access for the delivery of fluids, nutrition, or medication. Peripheral IV site complications, such as infiltration and phlebitis, account for the greatest risk to most patients receiving infusion therapy. These complications may result in substantial acute or chronic injury, which may be further exacerbated if the affected individual is a child. Evidence suggests that the implementation of bedside-nurse training and more frequent assessment will reduce the risk for peripheral IV site complications. This project evaluates the implementation of these interventions on a pediatric acute care unit.